SHORTEST ROUTE FOR DISTRIBUTION OF ELECTION LOGISTICS IN CILACAP REGENCY USING THE BRANCH AND BOUND ALGORITHM - Mizan Ahmad; Riski Aspriyani; Nadzifah; Umi Ma’rifah (PROCEEDING AL GHAZALI International Conference, 2023)
Distribution of election logistics requires a large budget. Therefore, distribution planning is needed to streamline the budget. One form of planning is in the form of planning the shortest distribution route. This research aims to determine the shortest route for distribution of election logistics in Cilacap Regency using the Branch and Bound Algorithm. Determining the distance between sub-districts in Cilacap Regency using the help of GoogleMaps. Based on the results of this research, the shortest route for distribution of election logistics in Cilacap Regency is 149.1 km for the first route and 335 km for the second route.